Morphological Study of Cocopet Euborellia arcanum (Order: Dermaptera) in the Muhammad Sabki Urban Forest Area, Jambi City - Putra, Dhean Primanda; Wulandari, Tia; Sakinah, Audriella Nadine; Suhanda, Robet (ORGANISMS: JOURNAL OF BIOSCIENCES, 2024)
Euborellia arcanum, an insect from the Dermaptera Order, plays a crucial ecological role as both a predator and a decomposer. However, the genus Euborellia is notoriously challenging to identify. Despite its ecological importance, studies on the genus Euborellia, particularly in Indonesia, remain limited. This study aimed to describe the morphological characteristic of E. arcanum as a reference for identification and scientific information. The study was conducted from August to September 2024 in the Muhammad Sabki Urban Forest Area, using direct sampling and morphological examination by microscopic approach. The Dermaptera Order is characterized by cerci, appendages at the abdomen's end, shaped like tweezers. E. arcanum, a wingless (apterous) species of Euborellia, measures 18–26 mm in total length, including forceps. Specimens collected in this study measured approximately 20 mm. E. arcanum has biting-chewing mouthparts, blackish-brown compound eyes for detecting light and movement, and filiform antennae with 19 antenomeres. The 12th to 15th antenomeres are yellow. The prothorax of E. arcanum is rectangular, slightly longer than wide, with a smooth surface. The mesothorax and metathorax are transverse, wider than long, and also have smooth surfaces. The abdomen consists of nine convex tergite segments, except for the last segment, which is transverse and slightly convex posteriorly. AbstrakEuborellia arcanum, serangga dari Ordo Dermaptera, memainkan peran ekologis yang sangat penting sebagai predator dan pengurai. Namun, genus Euborellia terkenal sulit untuk diidentifikasi. Meskipun memiliki peran ekologis yang penting, penelitian mengenai genus Euborellia, khususnya di Indonesia, masih sangat terbatas. Penelitian ini bertujuan untuk mendeskripsikan karakteristik morfologi E. arcanum sebagai acuan identifikasi dan informasi ilmiah. Penelitian dilakukan pada bulan Agustus hingga September 2024 di Kawasan Hutan Kota Muhammad Sabki, dengan menggunakan metode pengambilan sampel secara langsung dan pemeriksaan morfologi secara mikroskopis. Ordo Dermaptera memiliki ciri khas berupa cerci, pelengkap pada ujung abdomen yang berbentuk seperti pinset. E. arcanum, spesies Euborellia yang tidak bersayap (apterous), memiliki panjang total 18-26 mm, termasuk forsep. Spesimen yang dikumpulkan dalam penelitian ini berukuran sekitar 20 mm. E. arcanum memiliki bagian mulut yang menggigit dan mengunyah, mata majemuk berwarna coklat kehitaman untuk mendeteksi cahaya dan gerakan, dan antena filiform dengan 19 antena. Antena ke-12 hingga ke-15 berwarna kuning. Prothoraks E. arcanum berbentuk persegi panjang, sedikit lebih panjang dari lebar, dengan permukaan yang halus. Mesotoraks dan metatoraks melintang, lebih lebar daripada panjang, dan juga memiliki permukaan yang halus. Abdomen terdiri dari sembilan segmen tergit cembung, kecuali segmen terakhir yang melintang dan sedikit cembung ke arah posterior.